A social network analysis to explore collaborative practice in home care: research protocol - Chloé Schorderet; Caroline H. G. Bastiaenen; Henk Verloo; Robert A. de Bie; Lara Allet (BMC, 2022)
Abstract Background The conceptualization of the home as a care environment and maintaining a high standard of care requires different professionals to collaborate. This study will explore collaborative practice in home care, needs and expectations of the stakeholders involved, and identify their roles and tasks. Secondly, it will investigate possible strategies to improve home care management and, more particularly, optimize collaborative practice in home care. Methods The study will be conducted during three distinct consecutive phases, within a multiphase mixed-methods design. Phase 1 will use a quantitative approach in which a social network analysis will be conducted to have an overview of collaborative practice in home care in French-speaking Switzerland. Phases 2 and 3 will be qualitative and focus on three different situations involving different locations (rural and urban) and different home care functioning (home care provided by agencies and home care providing by independent caregivers). In each situation, semi-structured interviews will be conducted with home care recipients and their home caregivers. In phase 2, results of phase 1's network analysis will be discussed, such as roles, needs, and expectations of all stakeholders involved in home care. In phase 3, phase 2's findings will be discussed and strategies to improve home care and to optimize collaborative practice will be explored. Discussion Over the past years, home care has grown considerably. Therefore, more and more different caregivers are involved in the recipients' homes. Since optimal coordination between these different caregivers is a prerequisite for quality and safe care, it is essential to investigate the existing collaborative practice and how it is functioning. This study will provide knowledge on roles, needs and expectations of different caregivers involved in home care. It will also allow for strategies to optimize collaborative practice and thus ensure comprehensive care for recipients. Finally, it will serve as a basis for future studies that can be conducted to address identified needs.